IS256-Mediated Overexpression of the WalKR Two-Component System Regulon Contributes to Reduced Vancomycin Susceptibility in a Staphylococcus aureus Clinical Isolate - Kuroda, Makoto; Sekizuka, Tsuyoshi; Matsui, Hidehito; Ohsuga, Jun; Ohshima, Toshio; Hanaki, Hideaki (Frontiers in Microbiology, 2019)
Vancomycin (VAN)-intermediate-resistant Staphylococcus aureus (VISA) is continually isolated globally, with a systematic review suggesting a prevalence of 2% in all blood culture samples. Most VISA strains exhibit common characteristics, such as a thickened cell wall, reduced autolysis, and attenuated virulence. Here, based on multi-omics approaches, we have characterized clinical VISA isolates obtained through prolonged antimicrobial treatment in a single patient. All VISA isolates were isogenic, based on multi-locus sequence typing (MLST) ST5, SCCmec type II (2A), and spa type t17639. Core-genome single nucleotide variations (SNVs) found among thirteen isolates during the patient’s hospitalization, indicated clonality, but not notable genetic features of the VISA phenotype. We determined the complete genome sequence of VAN-susceptible strain KG-03 (minimum inhibitory concentration [MIC] 0.5 µg/mL) and two VISA strains, KG-18 and KG-22 (MIC 8.0 and 4.0 µg/mL, respectively). Comparative genome analysis showed remarkable strain-specific IS256 insertions. RNA-Seq transcriptome analysis revealed IS256-mediated overexpression of the walKR two-component system in VISA KG-18, possibly leading to modulation of cell wall integrity (lytM and sceD) and surface charge (mprF and dltABCD). In addition, secretome analysis indicated that cell wall-anchored proteins (Protein A, SasG, and SdrD) were significantly decreased. KG-18 and KG-22 exhibit thickened cell wall, and are relatively resistant to lysostaphin, which cleaves a staphylococcus-unique pentaglycine chain in the peptidoglycan. We conclude that KG-18 achieved reduced susceptibility to VAN by IS256-mediated WalKR overexpression, leading to a markedly thickened cell wall for trapping free VAN molecules with redundant D-Ala-D-Ala targets. In addition, a positively charged surface with lysyl-phosphatidylglycerol and depolarization of wall teichoic acid could contribute to inhibiting cationic daptomycin and VAN antimicrobial activity. Comparative omics approaches in this study strongly suggest that fully complete and annotated genome sequences will be indispensable for characterizing overall VISA phenotype.